RELATIONSHIP BETWEEN TRAINING AND DEVELOPMENT, GAYAKEPEMIMPINAN EMPLOYEES TO ACHIEVEMENT IN PURI ARTHA HOTEL YOGYAKARTA - Utami, Wiwit; Lastari, SE., MM, Siwi; Darini, M.Si., Dra. Sri (Management, 2010)
The study found that there is a positive relationship between training and development of work performance. This relationship is expressed by the correlation coefficient for 0485 with a smaller price rtabel with significance level of 5% (0485> 0339> 0.05). Training and development factors can be used to predict the level of employees´ performance of 23:52%. The relationship between leadership style on employees´ performance in this study were positive and there is a relationship that is based on giving different interpretations of the correlation coefficient. This leadership style shown by the style used by leaders when interacting with subordinates to work together to achieve company goals. This relationship is expressed by the correlation coefficient obtained for 0425 with prices rtabel = 0254 with a significant level of 5% (0.05). This leadership style factors can be used to predict high or low performance of 18:06%. Based on the multiple correlation analysis of obtained results for 0587 with prices Ftable 3.23. So the research hypothesis is accepted, where Fcount> Ftable> significant level (14 983> 3:23> 0.05). For the results of hypothesis testing, the third hypothesis is correct and all the researchhypothesis is accepted and all variables have a positive relationship Keyword leadership style,job performance